EVALUASI TINGKAT PELAYANAN MODA TRANSPORTASI AIR (PERAHU MOTOR ) PADA PELABUHAN PENYEBERANGAN BITUNG KE PULAU LEMBEH - Merta Maga; Djoni Agustaf; Prylita Rombot (Sustainable Construction (SUSCON), 2024)
The Bitung Ferry Port to Lembeh Island does not meet the feasibility standards in the aspects of safety, security, comfort, convenience and equality. One of the problems currently occurring at the Bitung Ferry Port is an example of a pier that does not meet suitability standards. Then, in an effort to improve aspects of safety, security, comfort, convenience and equality in organizing ferry transportation, minimum crossing service standards were prepared, namely PM No. 39 of 2015. Referring to this, port management must be in accordance with the specified aspects.